Multiple Omega Networks for Parallel Processing - Moreira, José Eduardo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1992)
In this paper we propose the use of multiple Omega networks as an interconnection system for shared memory multiprocessors. This allows us to achieve a much higher bandwidth of communication, accommodating the needs of current high-performance processors, including those with multiple memory ports. We also obtain a very scalable system, by defining a processor-switch-memory building block that can be used in systems with processor count in the range of a few units to several thousands. The performance evaluation of multiple Omega networks is clone through a simple analytical model that allows us to compare their performance to a that of a single network, and investigate alternatives for processors with multiple memory ports. The results show that the performance (in terms of bandwidth and latency of communication) of systems with multiple networks is more stable with respect to variations in systems parameters such as number of processors and memory access rate, than that of systems with just a single network.